2016
DOI: 10.1016/j.foodhyd.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound treatment on the structural, physical and emulsifying properties of animal and vegetable proteins

Abstract: 8The ultrasonic effect on the physicochemical and emulsifying properties of three animal proteins, 9 bovine gelatin (BG), fish gelatin (FG) and egg white protein (EWP), and three vegetable proteins, pea protein 10 isolate (PPI), soy protein isolate (SPI) and rice protein isolate (RPI), was investigated. Protein solutions (0.1 -11 10 wt. %) were sonicated at an acoustic intensity of ~34 W cm -2 for 2 minutes. The structural and physical 12 properties of the proteins were probed in terms of changes in size, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
195
2
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(231 citation statements)
references
References 60 publications
22
195
2
12
Order By: Relevance
“…Приготовление кондитерского теста на активированной кавитационно-магнитным способом белково-жировой эмульсии, сопровожда-ющееся гидратационной структуризацией белков, позволяет существенно увеличить удельный объем изделий, повысить их эластичность, замедлить черствение и сократить использование хлебопекарных улучшителей [11][12][13][14][15]. Под воз-действием магнитного поля и ультразвука водородные связи между молекулами воды заметно нарушаются, и образуется молекулярная вода, обладающая сильными проникающими свойствами и растворяющей способностью питательных веществ.…”
Section: для цитированияunclassified
“…Приготовление кондитерского теста на активированной кавитационно-магнитным способом белково-жировой эмульсии, сопровожда-ющееся гидратационной структуризацией белков, позволяет существенно увеличить удельный объем изделий, повысить их эластичность, замедлить черствение и сократить использование хлебопекарных улучшителей [11][12][13][14][15]. Под воз-действием магнитного поля и ультразвука водородные связи между молекулами воды заметно нарушаются, и образуется молекулярная вода, обладающая сильными проникающими свойствами и растворяющей способностью питательных веществ.…”
Section: для цитированияunclassified
“…Low frequency and high intensity of US can react to decrease the size of particles in bovine protein extracts, fish and bovine serum albumin (Gülseren et al, 2007;Sullivan et al, 2016). Gülseren et al (2007) also reported that free thiol groups were reduced 30% after the application of ultrasound in bovine serum albumin extracts, suggesting that ROS produced by sonication can react with albumin and thereby contribute to oxidative changes demonstrated.…”
Section: Ultrasound and Slightly Acidic Electrolyzed Water Effects Inmentioning
confidence: 99%
“…На основании полученных результатов исследований ультразвуковой и магнитной восприимчивости эмульсий показана возможность управления реологическими и структурными свойствами таких систем [2, 7,8]. Практическая ценность работы состоит в том, что снятые характеристики открывают возможности для теоре-тического построения моделей комбинированных устройств.…”
unclassified
“…и др.) с использованием ультразвука и синфазного магнитного поля значительно сокращает количество вводимых компонентов-эмульгаторов [7,8]. Способ харак-теризуется высокой устойчивостью эмульсии к расслоению и коалесценции за счет исключи-тельного мелкого диспергирования растительного жира в жидкой фазе, по диаметру жировых шариков, приближенных к молочным [8].…”
unclassified
See 1 more Smart Citation